PENGARUH KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA MIXUE GWALK - Gunardy, Geofrey; Padmawidjaja, Liestya (PERFORMA, 2024)
The aim of this research is to determine the effect of service quality on intention to revisit which is mediated by customer satisfaction. The development of the business world, including the Ice Cream business, recorded significant growth. One of the ice cream businesses that is growing very fast is Mixue. Mixue has 21,582 franchise stores in the world and approximately 10,000 outlets in Indonesia, one of which is Mixue which is in Gwalk, West Surabaya. The problem that occurs at Mixue Gwalk is that there are increasingly fewer buyers, so researchers conducted a pre-survey which was distributed to 39 respondents and on average respondents stated that they did not want to return to Mixue Gwalk because of the poor service quality, reinforced by Google reviews from several people who also stated that the quality of service was poor. The research was conducted using a Likert questionnaire which was distributed to 122 respondents aged 18 years and over who had visited Mixue Gwalk and made transactions. The type of research used is quantitative research, and in carrying out data analysis, SmartPLS 3.0 is used. The research method used is non-probability sampling, namely purposive sampling to take samples. Sampling was 122 samples. Based on this research, it is clear that service quality influences customer satisfaction, customer satisfaction influences repurchase intention, service quality influences repurchase intention, and customer satisfaction mediates the relationship between service quality and repurchase intention. So, it can be concluded that there are 4 hypotheses and all hypotheses are accepted. With this research, it is hoped that Mixue Gwalk can improve deficiencies in terms of service quality and customer satisfaction, meaning providing a comfortable and clean place, maintaining product consistency, providing fast service and paying attention to each customer, having a secure parking area, paying attention to product cleanliness, and cares about its customers.